1989
DOI: 10.1016/0014-5793(89)80629-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression of RNA transcripts for the postsynaptic 43 kDa protein in innervated and denervated rat skeletal muscle

Abstract: A cDNA clone encoding the mouse muscle postsynaptic 43 kDa protein was isolated and sequenced. The amino acid sequence of this protein, which is closely associated with nicotinic acetylcholine receptors at Torpedo electrocyte and vertebrate skeletal muscle synapses, is very similar in different species. A cysteine-rich region homologous to part of the regulatory domain of protein kinase C may be important in interactions of this protein with the lipid bilayer. RNA transcripts for the 43 kDa protein increase on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 49 publications
2
35
0
Order By: Relevance
“…Another sequence comparison (1) performed at the National Center for Biotechnology Information on the same data bases using the BLAST network service identified a cysteine-rich sequence close to the COOH terminus of Vpsl8p (residues 826 to 894) with sequence similarity to the 43-kDa postsynaptic protein (15) and certain zinc finger proteins (9). The pattern of cysteine residues is CX2CX13CX2CX4CX38CX2C (underlined in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another sequence comparison (1) performed at the National Center for Biotechnology Information on the same data bases using the BLAST network service identified a cysteine-rich sequence close to the COOH terminus of Vpsl8p (residues 826 to 894) with sequence similarity to the 43-kDa postsynaptic protein (15) and certain zinc finger proteins (9). The pattern of cysteine residues is CX2CX13CX2CX4CX38CX2C (underlined in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A portion of the COOH-terminal region of the Vpsl8p sequence is shown in Fig. 3 compared with cysteinerich sequences from the 43-kDa postsynaptic protein of rat (15), Vpsllp/Pep5p/Endlp (13,53), the adenovirus ElA protein (10), and Gal4p (36 …”
Section: Resultsmentioning
confidence: 99%
“…The probe hybridized with chick muscle transcripts of ϳ2.0, 4.0, and 6.0 kb (lanes D, E). In addition to the predominant species at 2.0 kb (Frail et al, 1988;Froehner, 1989), hybridization with larger transcripts has also been reported for Torpedo electrocytes and Xenopus embryos (Frail et al, 1987;Baldwin et al, 1988). Interestingly, the mouse rapsyn cDNA probe also hybridized with chick brain mRNA transcripts (lanes B, C).…”
Section: Northern Blot Hybridization Analysismentioning
confidence: 99%
“…mRNA was purified by two rounds of poly(A ϩ ) selection using affinity chromatography on oligo(dT)-cellulose (Sambrook et al, 1989), fractionated by electrophoresis on 1.0% agarose gels containing 6% formaldehyde, and transferred to Hybond-N nylon filter membranes (Amersham, Arlington Heights, IL). A mouse rapsyn cDNA insert, 1A15, obtained by deleting 5Ј untranslated sequences from M43K.1 to remove an upstream AUG (Froehner, 1989) was excised by digestion with SphI and EcoRI endonucleases and separated on a 1% agarose gel by electroelution into DEAE-cellulose membrane (NA45, Schleicher and Schuell, Keene, NH). Referred to here as M43K.1A, the insert was provided in pBluescript (Stratagene, La Jolla, CA) by Dr. Stanley Froehner (University of North Carolina).…”
Section: Methodsmentioning
confidence: 99%
“…Because of its localization and intimate relationship with AChR, it has been also hypothesized that expression of this protein may be markedly influenced by the presence of the motor nerve. In separate experiments, however, Frail et al [47] and Froehner [48] showed that denervation of rodent muscle resulted only in marginal increases in the expression of mRNA encoding the 43 kDa protein. These results obtained with a distinct cytoskeletal protein of the postsynaptic membrane are thus coherent with our observations.…”
Section: Discussionmentioning
confidence: 99%